Locating religions: contact, diversity, and translocality - Glei, Reinhold; Jaspert, Nikolas (Dynamics in the history of religions, 2017)
Preliminary Material -- Terms, Turns and Traps: Some Introductory Remarks /Reinhold Glei and Nikolas Jaspert -- Geography, History and Prophecy: Mechanisms of Integration in the Islamic Alexander Legend /Anna Akasoy -- The Portuguese Discovery of Buddhism: Locating Religion in Early Modern Asia /Stephen C. Berkwitz -- From Geographical Migration to Transmigration of Souls: Negotiating Religious Difference between Space among Jews in Early Modern Safed /Alexandra Cuffel -- Translocating Religion in the Mediterranean Space: Monastic Confrontation under Muslim Dominion /Ana Echevarría -- The Mirror and the Palimpsest: The Myth of Buddhist Kingship in Imperial Tibet /Georgios T. Halkias -- Prester John, the Ten Tribes, and the Raja Rum: Representing the Distant Ally in Three Pre-Modern Societies /Adam Knobler -- Locating Religion, Controlling Territory: Conquest and Legitimation in Late Ninth-Century Vaspurakan and its Interreligious Context /Zaroui Pogossian -- The Meeting of Daoist and Buddhist Spatial Imagination: The Construction of the Netherworld in Medieval China /Henrik H. Sørensen -- Locating the Dialogue: On the Topology of the Setting in Medieval Religious Colloquies /Knut Martin Stünkel -- Space, Entanglement and Decentralisation: On How to Narrate the Transcultural History of Christianity (550 to 1350 ce) /Dorothea Weltecke -- Armlet of the Pinnacle of the Noble Victory Banner: Locating Traces of Imperial Tibet in a Dhāraṇī in the British Museum /Michael Willis and Tsering Gonkatsang -- Index of Names and Places.